The Adaptive Liar: An Interactionist Approach of Multiple Dishonesty Domains - Ximena Garcia-Rada; Heather E. Mann; Lars Hornuf; Matthias Sohn; Juan Tafurt; Edwin S. Iversen Jr; Dan Ariely (Center for Economic Studies and ifo Institute (CESifo), 2018)
An extant debate in the morality literature centers on whether honesty is a stable and generalizable trait or whether honest behavior in one situation is independent from honest behavior in another situation. However, a third possibility is that tendencies toward dishonesty vary according to life domain. We conducted a cross-cultural study with participants in five countries (China, Colombia, Germany, Portugal, and the United States) to test whether dishonest tendencies vary according to domain. We hypothesized that countries vary in dishonesty according to domain, and that individuals' tendencies toward dishonesty cluster by domain. Our survey asked participants to report the likelihood of engaging in dishonest behaviors across eight domains of life. The data support both our hypotheses. Our results thus corroborate that dishonesty is driven by the interplay of both individual differences and the circumstances surrounding deception.
Keywords: C83; P51; 330; dishonesty; moral behavior; cross-cultural study